State of Charge Estimation for Lithium Polymer Batteries - Sihar, Nur Ain (Universiti Teknologi PETRONAS, 2016)
Lithium Polymer (Li-Po) batteries are commonly used as a rechargeable power source in mobile systems and remotely controlled. However, the common constraint of Li-Po batteries is that the battery units must be used within their limits during charging and discharging period. The inefficient use during charging or discharging will affect the lifetime and discharge rate of the battery. Therefore, correct state-of-charge (SOC) estimation of the battery can alert the user about the remaining voltage capacity and the need for re-charging. Thus, SOC indication helps to protect these batteries from being overcharged or being discharged beyond its limit.